Physico‐chemical characterization and in vitro digestibility of gelatinized corn starch dispersion fractions obtained by centrifugation. Issue 7 (22nd May 2015) - Vernon‐Carter, Eduardo J.; Hernandez‐Jaimes, C.; Meraz, Monica; Lara, Victor H.; Lobato‐Calleros, Consuelo; Alvarez‐Ramirez, Jose
<x xml:space="preserve">Abstract</x> Gelatinized corn starch dispersions (GSD) (5% w/w) were prepared by gently stirring and heating at 90°C for 20 min, cooled down to room temperature (18°C), and centrifuged at 2950×g. The supernatant fraction was optically transparent while the precipitate fraction had a waxy‐like appearance with reduced amylose content. After 7 days, the supernatant developed a milky‐like turbid appearance. Optical and confocal microscopy showed that the supernatant fraction had needle‐like crystalline morphology that agglomerated about lamellar structures after drying. SAXS analysis was performed to confirm the geometry and fractality of the dried agglomerates obtained from the supernatant. XRD and FTIR analyses indicated reduced crystallinity of the precipitate, suggesting the dominance of amorphous structures. Digestibility test showed that the precipitate was more prone to rapid digestibility than the original GSD.